GAMBARAN MOTIVASI BEKERJA PERAWAT DALAM MASA PANDEMI CORONAVIRUS DISEASE (COVID-19) DI BALI - Darma Yanti, Ni Putu Emy; Susiladewi, Ida Ayu Made Vera; Pradiksa, Hary (Coping: Community of Publishing in Nursing, 2020)
A professional nurse must have an obligation to care for all kinds of patients in various conditions, various need, including the COVID-19 pandemic. Nurses' concerns about their work have its impact on themselves which is can reduce nurses' work motivation. This study aims to describe the work motivation for nurses during the COVID-19 pandemic in Bali. This type of research is quantitative with a descriptive survey design on 193 nurses in Bali through purposive sampling technique. The results of data analysis found that the majority of nurses' work motivation during the COVID-19 pandemic was in the good category, namely 52.8%. The majority of nurses answered that they agreed on every item of the statement given regarding the work motivation of nurses except for points oneand two. The statement on point one "The compensation I receive will affect my performance for the better", most of the study participants answered strongly agree, namely 45.1%. While the statement of point two is "The compensation I have received so far has been in accordance with my workload", the majority of study participants answered "Disagree", namely 40.9%. The good work motivation of nurses during the COVID-19 pandemic is expected to increase nurses' confidence in providing nursing care to COVID-19 patients.